Civil Servant Compensation System Reform In Indonesia - Simanungkalit, Janry Haposan U.P (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
Analysis of Civil Servant compensation system attracts attention of many parties. There opinion going that low salary has contributed to bad performance and productivity. Moreover Civil Servant management causing social cost and high cost economy. It becomes an excuse for undisciplined behavior and triggers such “deviation” deed resulted inefficiency and ineffectiveness of bureaucracy and “threatens” to break down actualization of bureaucracy reform as a whole. Many attempts have been tried by Government such as “remuneration” policy in Central Government Agencies and performance “subsidy” in Local Government Agencies. However, instead of being solution, this acts cause another problems. The objectives of analysis in this paper are: giving description and remapping various problems connected to Compensation System and offering alternative design of it Compensation System in frame of civil service management. The results of the analysis end up in design scenario of Compensation System integrating the whole system inside. Solution to Performance Assistance in Bureaucracy Reform “package” will also formulated through asserting that it will given based on performance. Besides, legal aspects will straightened up to provide powerful legitimacy and simplification of various regulations, clarify and affirm components of compensation, including Pension and Retirement Subsidy System.